DESIGNING WITH SEVEN SEGMENT USE PROGRAMMABLE PERIPHERAL INTERFACE (PPI) 8255-BASED PC - Aldris Firmansyah; Nenny Anggraini, Skom, MT (Jurnal Sistem Komputer, 2006)
Combination "DESIGNING WITH SEVEN SEGMENT use programmablePERIPHERAL INTERFACE (PPI) 8255-based PC", is a series composed of PCs,interface 8255, and a series of seven segment interconnected with each other serves tobridge the 8255 PPI anatra computer with seven Combination segment. This circuit isused to display the data in the form of digital numbers and the output can then beviewed on the seven segment.For data processing in this circuit using the language C.